The moral problem: A correction to the key thought - Jackson Frank (Belgrade Philosophical Annual)
I argue that the three drugs example makes trouble for the role Smith gives to being fully rational in his solution to the moral problem, given his understanding of what it takes to be fully rational. I conclude by suggesting he might have drawn on a different understanding of what it takes to be fully rational.